Pengaruh Social Media Marketing dan Brand Image terhadap Keputusan Pembelian Produk Skintific di Kota Bandung - Zahra Annisa Nais; Angga Nadiyanto Prastian (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to determine and analyze the effect of Social Media Marketing and Brand Image on the purchasing decision of Skintific products among consumers in Bandung City. The research method used is a quantitative method with descriptive and verificative approaches. The sample in this study consisted of 100 respondents determined through a purposive sampling technique. Data processing and analysis were conducted using multiple linear regression analysis with the assistance of IBM SPSS Statistics 25 software. The results showed that Social Media Marketing and Brand Image have a positive and significant effect on purchasing decisions, both partially and simultaneously. The partial test results yielded a calculated t-value of 7.086 for the Social Media Marketing variable and 6.911 for the Brand Image variable. Meanwhile, the simultaneous test results showed a calculated F-value of 53.270 with a coefficient of determination (R^2) of 0.523. Based on these findings, it can be concluded that Social Media Marketing and Brand Image play an important role in influencing and increasing the purchasing decision of Skintific products.